2011
DOI: 10.1021/ic2005979
|View full text |Cite
|
Sign up to set email alerts
|

Redox Noninnocence of Nitrosoarene Ligands in Transition Metal Complexes

Abstract: Studies on the coordination of nitrosoarene (ArNO) ligands to late-transition metals are used to provide the first definition of the geometric, spectroscopic, and computational parameters associated with a PhNO electron-transfer series. Experimentally, the Pd complexes PdCl(2)(PhNO)(2), PdL(2)(PhNO)(2), and PdL(2)(TolNO) (L = CNAr(Dipp2); Ar(Dipp2) = 2,6-(2,6-(i)Pr(2)C(6)H(3))(2)-C(6)H(3)) are characterized as containing (PhNO)(0), (PhNO)(•1-), and (TolNO)(2-) ligands, respectively, and the structural and spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
111
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(115 citation statements)
references
References 73 publications
4
111
0
Order By: Relevance
“…49 X-ray crystallography, X-ray absorption spectroscopy (XAS), and computational studies indicated that, in the solid state, complex 1a possessed a divalent palladium center and two monoanionic nitroxide radicals. 52 In addition, magnetic susceptibility measurements on crystalline samples of 1a showed that the nitroxide radicals exhibit weak antiferromagnetic coupling mediated by superexchange across the Pd center resulting in a ground-state, open-shell singlet (i.e., singlet diradical) and a triplet excited state that is thermally accessible at ca. 290 K (singlet−triplet gap = 0.4 kcal/mol).…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…49 X-ray crystallography, X-ray absorption spectroscopy (XAS), and computational studies indicated that, in the solid state, complex 1a possessed a divalent palladium center and two monoanionic nitroxide radicals. 52 In addition, magnetic susceptibility measurements on crystalline samples of 1a showed that the nitroxide radicals exhibit weak antiferromagnetic coupling mediated by superexchange across the Pd center resulting in a ground-state, open-shell singlet (i.e., singlet diradical) and a triplet excited state that is thermally accessible at ca. 290 K (singlet−triplet gap = 0.4 kcal/mol).…”
Section: ■ Introductionmentioning
confidence: 99%
“…While the solid-state structure of Pd(κ 1 -N-PhNO) 2 -(CNAr Dipp2 ) 2 (1a) is established by X-ray crystallography and combustion analysis, as noted above, preliminary observations of its spectroscopic signatures in solution were inconsistent with its established magnetic properties. 52 Dissolution of forest green crystals of Pd(κ 1 -N-PhNO) 2 (CNAr Dipp2 ) 2 (1a) in benzene-d 6 or deuterated tetrahydrofuran (THF-d 8 ) produces a deep red solution. Analysis by 1 H and 13 C{ 1 H} NMR spectroscopy reveals the prominence of diamagnetic species in solution, with only one Ar Dipp2 environment apparent.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[22] Thus, innocence or non-innocence is not the permanent attribute of a ligand, but molecules can behave [8] as innocent or non-innocent ligands towards redox-active metals under specific circumstances, in a certain situation. While the potential for non-innocent ligand behavior is obvious for the very easily reducible and correspondingly employed TCNQ acceptor, [21] or for nitrosoarenes, [23] there are ligands with less eye-catching non-innocence. For instance, the substitutional modification [24] of the "NacNac" ligand [24] in [MeNC(Me)C(H)C(Me)NMe] -has made it potentially redox-active, i.e.…”
mentioning
confidence: 99%
“…Additionally,t he nitroxide aryl groups in complexes 8-10 adopt an in-plane orientation relative to the Mn center ( Figure 2B). This feature contrasts distinctly with structurally characterized h 2 -N,O nitrosoarene complexes (such as metalloxaziridines), [36] in which the aryl groups adopt aperpendicular orientation relative to the metal center on account of inplane M!p*(NO) backbonding.Accordingly,the solid-state structures of complexes 8-10 strongly suggest that the h 2 -ArNO ligands do not bind according to the standard DewarChatt-Duncanson model of M!L p backbonding.R ather, the structural properties of 8-10 indicate that the h 2 -ArNO ligands function as L 2 -type,n ot X 2 -type,d onors, [37] with an unpaired electron localized in aN Op*orbital oriented perpendicular to the plane of the Mn center. Ther oomtemperature EPR spectra of complexes 8-10 in toluene solution support this description and give rise to g iso values of 2.004, 2.008, and 2.005, respectively,i ndicative of organic radicals (see Figure 2C for the EPR spectrum of 8 and Figures S2.3 and S2.4 for the spectra of 9 and 10,r espectively).…”
Section: Angewandte Chemiementioning
confidence: 62%
“…Ther oomtemperature EPR spectra of complexes 8-10 in toluene solution support this description and give rise to g iso values of 2.004, 2.008, and 2.005, respectively,i ndicative of organic radicals (see Figure 2C for the EPR spectrum of 8 and Figures S2.3 and S2.4 for the spectra of 9 and 10,r espectively). Notably,w hile persistent nitroxide radical complexes are uncommon, structurally characterized examples exhibiting k 1 -N, [36,38,39] k 1 -O, [40] and bridging m-(1k 1 -N:2k 1 -O) [41] coordination modes have been reported. However,c omplexes 8-10 are unique examples of side-on bound h 2 -N,O nitroxide radicals.…”
Section: Angewandte Chemiementioning
confidence: 99%